Bioinspired Graphene Actuators Prepared by Unilateral UV Irradiation of Graphene Oxide Papers - Han, Dong-Dong; Zhang, Yong-Lai; Liu, Yan; Liu, Yu-Qing; Jiang, Hao-Bo; Han, Bing; Fu, Xiu-Yan; Ding, Hong; Xu, Huai-Liang; Sun, Hong-Bo (Advanced functional materials, 2015)
Inspired by natural autonomous systems that demonstrate controllable shape, appearance, and actuation under external stimuli, a facile preparation of moisture responsive graphene‐based smart actuators by unilateral UV irradiation of graphene oxide (GO) papers is reported. UV irradiation of GO is found to be an effective protocol to trigger the reduction of GO; however, due to the limited light transmittance and thermal relaxation, thick GO paper cannot be fully reduced. Consequently, by tuning the photoreduction gradient, anisotropic GO/reduced GO (RGO) bilayer structure can be easily prepared toward actuation application. To get better control over the responsive properties, GO/RGO bilayer paper with a certain curvature and RGO patterns are successfully prepared for actuator design. As representative examples, smart humidity‐driven graphene actuators that mimic the cilia of respiratory tract and tendril climber plant are successfully developed for controllable objects transport. A facile preparation of graphene actuators by unilateral UV irradiation of graphene oxide (GO) papers is reported. Anisotropic GO/reduced GO bilayer paper can be directly prepared by controlling the photoreduction gradient. As typical examples, smart humidity‐driven graphene actuators that mimic the cilia of respiratory tract and the tendril climber plant are developed for object transport.